2018
DOI: 10.1177/1541931218621427
|View full text |Cite
|
Sign up to set email alerts
|

80 MPH and out-of-the-loop: Effects of real-world semi-automated driving on driver workload and arousal

Abstract: The introduction of semi-automated driving systems is expected to mitigate the safety consequences of human error. Observational findings suggest that relinquishing control of vehicle operational control to assistance systems might diminish driver engagement in the driving task, by reducing levels of arousal. In this study, drivers drove a Tesla Model S with Autopilot in both semi-automated and manual modes. Driver behavior was monitored using a combination of physiological and behavioral measures. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…Additionally, it is noted that physiological measures and the NASA Task Load Index capture only certain facets of stress and workload. Recent on-road research indicated that using the Tesla Autopilot is associated with higher response times on a secondary task as compared to manual driving, possibly due to monitoring demands (e.g., monitoring of the roadway or automation status) or difficulty with multitasking (Biondi, Lohani, Hopman, Mills, Cooper, & Strayer, 2018;Stapel et al, 2019). Also, it remains to be studied how our findings generalize to other driving scenarios, such as driving during rush hours.…”
Section: Conclusion and Recommendationsmentioning
confidence: 80%
“…Additionally, it is noted that physiological measures and the NASA Task Load Index capture only certain facets of stress and workload. Recent on-road research indicated that using the Tesla Autopilot is associated with higher response times on a secondary task as compared to manual driving, possibly due to monitoring demands (e.g., monitoring of the roadway or automation status) or difficulty with multitasking (Biondi, Lohani, Hopman, Mills, Cooper, & Strayer, 2018;Stapel et al, 2019). Also, it remains to be studied how our findings generalize to other driving scenarios, such as driving during rush hours.…”
Section: Conclusion and Recommendationsmentioning
confidence: 80%
“…Variations in drowsiness levels can also impact HRV (Noda et al, 2015; Piotrowski and Szypulska, 2017). Another recent study found that variations in HRV (TINN and RMSSD) was higher when participants drove a vehicle in automated mode relative to the manual mode (Biondi et al, 2018). Perhaps, drowsiness and a lack of engagement in the driving task during automated mode may have led to a higher HRV.…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 99%
“…Drowsiness experienced in car drivers and aircraft pilots can also be associated with decreases in HR (Borghini et al, 2014 ). A recent on-road study (Biondi et al, 2018 ) found that driving a Tesla in semi-automated mode (e.g., autopilot) led to a lower heart rate relative to manual driving on a freeway. Another study found heart rate was sensitive to activity of the Adaptive Cruise Control (ACC) technology (Brouwer et al, 2017 ).…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 99%
“…To identify and exclude moments with excessive movements, accelerometer data should be collected together with the HRV. It is worth noting that it is possible to perform other measurements in conjunction with ECG patch devices [ 25 , 26 ]. However, it is necessary to consider the electromagnetic effect on increased background noise upon the ECG signal [ 27 , 28 ].…”
Section: Methods and Challenges For Cardiac Monitoring In The Antamentioning
confidence: 99%